On the semantic content of grammatical gender and its impact on the representation of human referents - Stockhausen, Lisa von; Kurovskaja, Julia (Experimental psychology, 2010)
Grammatical gender has been shown to provide natural gender information about human referents. However, due to formal and conceptual differences between masculine and feminine forms, it remains an open question whether these gender categories influence the processing of person information to the same degree. Experiment 1 compared the semantic content of masculine and feminine grammatical gender by combining masculine and feminine role names with either gender congruent or incongruent referents (e.g., Dieser Lehrer [masc.]/Diese Lehrerin [fem.] ist mein Mann/meine Frau; This teacher is my husband/my wife). Participants rated sentences in terms of correctness and customariness. In Experiment 2, in addition to ratings reading times were recorded to assess processing more directly. Both experiments were run in German. Sentences with grammatically feminine role names and gender incongruent referents were rated as less correct and less customary than those with masculine forms and incongruent referents. Combining a masculine role name with an incongruent referent slowed down reading to a greater extent than combining a feminine role name with an incongruent referent. Results thus specify the differential effects of masculine and feminine grammatical gender in denoting human referents.
Gesehen am 30.06.2023